2016
DOI: 10.1111/eff.12317
|View full text |Cite
|
Sign up to set email alerts
|

Cohort‐specific variation in juvenile coho salmon habitat use

Abstract: In this study, we examined summer and fall freshwater rearing habitat use by juvenile coho salmon (Oncorhynchus kisutch) in the quickly urbanising Big Lake drainage in south-central Alaska. Habitat use was assessed by regressing fish count data against habitat survey information across thirty study sites using generalised linear mixed models. Habitat associations were examined by age-0 and age-1+ cohorts separately, providing an opportunity to compare habitat use across different juvenile coho salmon life stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Minnow traps (metal mesh cylinders with cone-shaped openings on each end; Figure 1) have long been used to sample stream-dwelling juvenile salmonids in Alaska and elsewhere (Murphy et al 1986;Wipfli 1997;Bradford et al 2001;Rinella et al 2012;Bradley et al 2017;Campbell et al 2020). Minnow traps are often the most practical sampling gear in small streams because snags (brush, rocks, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minnow traps (metal mesh cylinders with cone-shaped openings on each end; Figure 1) have long been used to sample stream-dwelling juvenile salmonids in Alaska and elsewhere (Murphy et al 1986;Wipfli 1997;Bradford et al 2001;Rinella et al 2012;Bradley et al 2017;Campbell et al 2020). Minnow traps are often the most practical sampling gear in small streams because snags (brush, rocks, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Researchers frequently use salmon roe to bait minnow traps when they are targeting juvenile salmonids. Techniques for preparing the roe vary from study to study, with some using raw fresh or frozen roe (e.g., Wipfli 1997;Bradford et al 2001;Campbell et al 2020) or roe cured by various, sometimes unspecified, methods (e.g., Bloom 1976;Sethi and Benolkin 2013;Bradley et al 2017). Sport anglers commonly use roe that is cured with mixtures of salts, sugars, dyes, and various preservatives to target adult salmon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have described juvenile coho salmon habitat use and growth at local scales and within seasons. Summer studies demonstrate juvenile coho salmon predominately utilize stream habitats for rearing (Armstrong & Schindler, 2013; Bradley, Sethi, et al 2017; Foley et al, 2018), with substantial growth achievable over this short period (Armstrong & Schindler, 2013; Kahler et al, 2001). Fall and early winter studies indicate preferential distribution of juvenile coho salmon among lentic off‐channel or lake habitats (Peterson, 1982; Sethi & Benolkin, 2013; Swales et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…>2% slope) headwater tributaries in the subarctic Little Susitna basin in Alaska, although this life history was considered rarer than mainstem summer‐rearing behaviours. Bradley et al (2017) found that juvenile coho salmon were widely distributed throughout lotic reaches during summer rearing in the Big Lake, Alaska drainage, with evidence of age‐specific preference for shallower reaches with instream vegetation by young‐of‐year fish and deeper pools by older juvenile cohorts. Baldock et al (2016) and Armstrong & Schindler (2013) similarly found reliance on main channel reaches by juvenile coho salmon during summer months in the Bristol Bay region, with evidence of frequent localized migrations to off‐channel habitat to exploit advantageous water temperatures or to avoid high water‐flow pulses.…”
Section: Introductionmentioning
confidence: 99%